Osman Lins: a economia da natureza e a terra por vir - Joao Guilherme Dayrell de Magalhaes Santos (2015)
This thesis aims at expose and define how Osman Lins, a writer from Pernambuco (1924-1978), suggests the pathos in terms of animality, especially considering the works Nove, novena (1966) and Avalovara (1973). In these works we encounter a complex ecological disposal and, on the other hand, there is a critical proposal, an inventory of anthropo-technologies under the character of order and accuracy, present in themes such as alchemy, geometry, the glass eye and temperance, among others. We emphasize that the relationship between culture and nature in his work is a coincident point, significantly present in the literary criticism inspired by his books, although exhaustively unexplored. To this end, we conducted, following the footsteps of this literary criticism, an archeology of this topic in his texts. Moreover, it is intended that the topic stems mainly from Lins' criticism on Carl Jung's (archetype) and the French nouveaux romanciers (subjective realism) attraction to the phenomenology idea of Edmund Husserl, as well as the opposition between chaos and order, sensitive and intelligible, body and spirit, passive and active, positive and negative, physics and metaphysics in the Western canon (Plato, monotheism, Dante). Henceforth, we infer the writer's (Lins) passage through this tradition, which we could summarize as the charge of an economy of nature in civilization. From that point in time, we propose a stronger adherence of the author to poetic-literary Latin American tradition (especially in the work of João Cabral de Melo Neto) and to procedures of indigenous peoples exemplified by chroniclers, anthropologists and other scholars, resulting in an intensification of sense experience and constant reinvention of man's relationship with the surrounding environment. Both of these relationships are established by the advent of the shadow as an element in his literature. Finally, we will allocate such procedures under the 'Osmanian' proposal of the land to come.